Implementation of CT and IHT Processors for Invariant Object Recognition System - Turan, Jan; Ovsenik, L'ubos; Benca, Martin; Turan, Jan, Jr. (Radioengineering Society, 2004)
This paper presents PDL or ASIC implementation of key modules of invariant object recognition system based on the combination of the Incremental Hough transform (IHT), correlation and rapid transform (RT). The invariant object recognition system was represented partially in C++ language for general-purpose processor on personal computer and partially described in VHDL code for implementation in PLD or ASIC.
Keywords: Invariant object recognition; feature extraction; Hough and Rapid transform; PLD and ASIC imple-mentation